2016
DOI: 10.1080/13880209.2016.1228683
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of glycation-induced multiple protein modifications by Indian antidiabetic plant extracts

Abstract: P. crispum, B. diffusa and T. chebula had the most potent antiglycation activity. These plant exerted noticeable antiglycation activity at different glycation modifications of albumin. These findings are important for identifying plants with potential to combat diabetic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…G. glabra extracts exhibit up to 75% antiglycation potential. Another study reported the 69% glycation inhibition from G.glabra roots owing to the presence of triterpenoid saponin and glycyrrhizin that reduced level of advanced glycation end products (Tupe et al, 2017). Significant (p<0.05) alpha amylase inhibition ranged from 7.2 to 38.7%.…”
Section: Antidiabetic Potentialmentioning
confidence: 99%
“…G. glabra extracts exhibit up to 75% antiglycation potential. Another study reported the 69% glycation inhibition from G.glabra roots owing to the presence of triterpenoid saponin and glycyrrhizin that reduced level of advanced glycation end products (Tupe et al, 2017). Significant (p<0.05) alpha amylase inhibition ranged from 7.2 to 38.7%.…”
Section: Antidiabetic Potentialmentioning
confidence: 99%
“…Diabetes mellitus (DM) is one of the most deadly diseases in the world; its rate coupled with its complications increases with time in every part of the world [1]. This is a metabolic disorder that result from excessive accumulation of glucose in the blood due to either deficiency in insulin synthesis or defects in insulin receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have demonstrated 2,2‐diphenyl‐1‐picrylhydrazyl (DPPH) radical scavenging activity, protection against DNA damage, α‐amylase inhibitory effect of the plant and anti‐inflammatory properties (nitric oxide and tumour necrosis factor‐α inhibition) . Although this plant has also been shown to have a host of beneficial biological effects, including anti‐angiogenic and antidiabetic activity as well as protection against development of cardiac hypertrophy, its effect on cell migration has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%